A real-world study of Afatinib plus ramucirumab in treatment-naïve, EGFR-mutated, non–small cell lung cancer - Chun-Yao Huang; Hui-Li Huang; Chou-Chin Lan; Yi-Chih Huang; Yao-Kuang Wu (BMC Cancer, 2023)
Abstract Background Recent reports suggested combining ramucirumab with epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) to overcome EGFR resistance in non–small cell lung cancer (NSCLC). Nonetheless, evidence supporting the activity of afatinib and ramucirumab is lacking. This study investigated the survival benefits and safety profile of afatinib plus ramucirumab in patients with treatment-naïve, EGFR-mutated, metastatic NSCLC. Materials and methods The medical records of patients with EGFR-mutated NSCLC were retrospectively retrieved. Patients who received first-line sequential afatinib followed by ramucirumab and the first-line combination of afatinib plus ramucirumab were included. The Kaplan-Meier was used to estimate the progression-free survival (PFS) of all included patients, patients on sequential afatinib followed by ramucirumab (PFS1), and patients on the up-front combination of afatinib and ramucirumab (PFS2). Results Thirty-three patients were included (25 women; median age: 63 [45–82] years). The median follow-up of the included patients was 17 months (range 6–89 months). the median PFS for the whole cohort was 71 months (95% CI 67.2–74.8) with eight events during the follow-up. The median PFS1 and PFS2 were 71 months (95 CI not defined) and 26 months (95% CI 18.6–33.4), respectively. In terms of OS, the median OS for all patients and patients on sequential treatment was not defined, while the median OS for patients on upfront combination was 30 months (95% CI 20.9–39.1). There was no significant association between EGFR mutation type and PFS1 or PFS2. Conclusions Afatinib plus ramucirumab could improve the PFS of patients with EGFR-positive NSCLC at a predictable safety profile. Our data also suggest a survival benefit of adding ramucirumab to afatinib in patients with uncommon mutations, which should be investigated further.